2003
DOI: 10.1016/s1471-4906(03)00067-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel IL-12 family members shed light on the orchestration of Th1 responses

Abstract: Interleukin-12 (IL-12), which is composed of a p35 and a p40 subunit, is a proinflammatory natural-killer (NK) cell-stimulating, Th1-inducing and Th1-maintaining cytokine, which promotes cell-mediated immunity. On activation, heterodimeric IL-12 is found in small amounts, whereas free p40 is produced in excess. Besides IL-12, other p40-dependent molecules exist that orchestrate Th1 responses. Homodimeric p40 can act as an IL-12 antagonist by competing for its receptor. Recent data also reveal potential immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
178
1
7

Year Published

2004
2004
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(191 citation statements)
references
References 67 publications
4
178
1
7
Order By: Relevance
“…Moreover, both agonistic and antagonistic activities have been ascribed to (p40) 2 homodimers (35). In agreement with literature reports, we found IL-12p40 to be produced in large excess over IL-12p70 following infection with type II strain parasites (36).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, both agonistic and antagonistic activities have been ascribed to (p40) 2 homodimers (35). In agreement with literature reports, we found IL-12p40 to be produced in large excess over IL-12p70 following infection with type II strain parasites (36).…”
Section: Discussionsupporting
confidence: 92%
“…Although it is possible that early, transient, and low-level IL-12 responses might have been missed (as suggested by the flow cytometric analysis in which IL-12-positive cells could be detected after 18 h of incubation with iRBC), it also seems likely that an initial wave of IFN-␥ markedly up-regulates the IL-12 response and that this in turn may further augment the IFN-␥ response, leading to a positive feedback loop from which very high concentrations of proinflammatory cytokines can result. In contrast, previous in vitro studies have reported rapid in vitro induction of IL-12p40 upon stimulation of PBMC with iRBC (4,46), raising the interesting possibility that one of the first cytokines to be induced by iRBC may be IL-23 (a heterodimer composed of p40 and p19) or possibly even IL-27, which contains a p40-related protein (53). Intriguingly, IL-27 has been shown to induce IFN-␥ production by human NK cells independently of, and before IL-12 (54), suggesting that the potential role of this cytokine in the early response to iRBC requires further investigation.…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, it is also possible that distinct ligands, such as IL-27 (p28 plus EBI-3) vs EBI-3 plus p35 of IL-12 (24,34), bind to the WSX-1 receptor complex in various settings (see Ref. 35 for review). From these points, it is intriguing that mice lacking EBI-3 (a subunit of IL-27) showed defects in NKT cell development (31).…”
Section: Discussionmentioning
confidence: 99%
“…Memory CD4 ϩ T cells resort to IL-23/IL-23R for their proliferation and augmentation of IFN-␥ production (for review, see Refs. [35][36][37]. However, the roles played by members of the expanding IL-12 family are not limited to Th1 differentiation and IFN-␥ production.…”
Section: Discussionmentioning
confidence: 99%